2011
DOI: 10.1128/aem.05203-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucosyltransferase B in Interactions of Candida albicans with Streptococcus mutans and with an Experimental Pellicle on Hydroxyapatite Surfaces

Abstract: Candida albicans and mutans streptococci are frequently detected in dental plaque biofilms from toddlers afflicted with early childhood caries. Glucosyltransferases (Gtfs) secreted by Streptococcus mutans bind to saliva-coated apatite (sHA) and to bacterial surfaces, synthesizing exopolymers in situ, which promote cell clustering and adherence to tooth enamel. We investigated the potential role Gtfs may play in mediating the interactions between C. albicans SC5314 and S. mutans UA159, both with each other and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(231 citation statements)
references
References 58 publications
7
218
0
2
Order By: Relevance
“…The half-life of most proteins is in the range of 24 h, whereas that of mRNA is around 5 min (Moran et al, 2013). Excreted glucosyltransferases have been shown to be active on Candida surfaces (Gregoire et al, 2011) and thus are likely to have been operating although their transcription was rapidly downregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life of most proteins is in the range of 24 h, whereas that of mRNA is around 5 min (Moran et al, 2013). Excreted glucosyltransferases have been shown to be active on Candida surfaces (Gregoire et al, 2011) and thus are likely to have been operating although their transcription was rapidly downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…A tight co-aggregation between C. albicans and streptococci has been observed (Jenkinson et al, 1990;Metwalli et al, 2013) and could be owing to specific adhesins similar to those found in S. gordonii (Silverman et al, 2010) or to a glucan layer formed on the Candida cells by the glucosyltransferase B (GtfB) exoenzyme (Gregoire et al, 2011). Interaction between C. albicans and streptococci can contribute to enhanced biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…The exoenzyme glucosyltransferases (Gtfs) are predominantly responsible for the production of α-glucans from dietary sugar, and it is known that these extracellular polysaccharides are the key mediators of these dual-species cariogenic biofilms. In the absence of sucrose, C. albicans demonstrates a weak co-aggregation with S. mutans; however, secreted Gtfs from S. mutans establishes a co-aggregation between these two organisms, binding with high affinity [61,62]. The increased ECM biovolume within the dual-species biofilm actively contributes to the pathogenicity of disease, with increased levels of infection and carious lesions observed in vivo [60].…”
Section: Caries: Slimy Residentsmentioning
confidence: 99%
“…In addition to synthesizing different glucans, GtfBCD also have distinct roles in the building of dental plaque. GtfC is absorbed to enamel, GtfB binds to bacteria or fungi and enhances adhesion to plaque, and GtfD catalyzes the biosynthesis of a soluble polysaccharide, which acts as a primer for GtfB (Bowen and Koo 2011;Gregoire et al 2011). Since the diverse glycosyl linkage products are determined by limited differences in the conserved catalytic domain, the distinct roles in the formation of dental plaque can be attributed to low homology among putative glucan binding modules found in each GTF.…”
Section: Glucosyltransferases That Catalyze the Synthesis Of Glucans mentioning
confidence: 99%